PENGARUH RASIO LIKUIDITAS, PROFITABILITAS, DAN LEVERAGE TERHADAP FINANCIAL DISTRESS - Widiastuti Widiastuti; Ali Nur Ikhsan (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to determine the effect of Liquidity Ratio, Profitability ratio, and Leverage ratio on Financial Distress in Road Transportation Sub-Industry Transportation Sector Companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021 partially. The data used is secondary data from 2017-2021. The data obtained is then processed using the Eviews 12 analysis tool. The analytical methods used are descriptive analysis, classical assumption test, panel data regression analysis and hypothesis testing. The results of this study indicate that partially the liquidity ratio with a proxy (current ratio) has an effect on financial distress. Likewise, the profitability ratio with the return on assets (ROA) proxy has an effect on financial distress. While the leverage ratio with the debt to equity ratio (DER) proxy has an effect on Financial Distress.